Constrained by markets: processing costs limit potential for managing predator-prey interactions in a commercial fishery - Walsworth, Timothy E.; Schindler, Daniel E.; Essington, Timothy E. (The Journal of applied ecology, 2017)
1. Selective fisheries may impact non-target species as well as limit the productivity of target species if their predators are not harvested. The outcomes of multi-species harvest strategies that include targeting predators depend on ecological and economic constraints, although the development of ecosystem-based management plans has typically focused on ecological constraints. 2. In Chignik, Alaska, sockeye salmon support a valuable commercial fishery and, as juveniles, are preyed upon by coho salmon, a species not subject to a targeted harvest. Whether exploitation of coho salmon would enhance overall fishery value by releasing sockeye salmon from predation constraints is not understood. We employ simulation models to examine the ecological and economic conditions necessary for directly targeting coho salmon to benefit fishers and seafood processors, two distinct but inter-dependent stakeholders in this ecosystem. 3. Model results indicate fishers are likely to experience increased value regardless of economic constraints, as long as coho salmon prédation negatively affects sockeye salmon productivity. However, seafood processors are much more limited in the conditions which produce increased economic value, constrained by greater operation costs required to process harvested coho salmon. 4. Synthesis and applications. The unique economic constraints and opportunities of different stakeholders can present contrasting outlooks on the potential benefits of alternative harvest strategies, even if the alternative strategies are predicted to increase yield. The findings herein demonstrate the importance of considering multiple stakeholders when considering alternative management strategies. Depending on the level of risk stakeholders are willing to accept, an active adaptive management strategy reducing coho salmon escapement to low levels could provide valuable information about ecosystem structure as well as potentially providing the greatest economic benefit to the fishery.